Philippine Ethnography A Critically Annotated and Selected Bibliography - Saito, Shiro (University of Hawai'i Press, 1972)
This volume is a comprehensive listing of reference sources for Philippine ethnology, excluding physical anthropology and de-emphasizing folklore and linguistics. It is published as part of the East-West Bibliographic Series. This listing includes books, journal articles, mimeographed papers, and official publications selected on the basis of the ratings of sixty-two Philippine specialists. Several titles were added to fill the need for material in certain areas.